The Characters of Special Region According to The 1945 Constitution of Republic of Indonesia - Asep Bambang Hermanto; Anggara Suwahju (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2019)
The Republic of Indonesia, based on the 1945 Constitution, the second Amendment, recognizes the existence of a Special Region and its distinctive governance. Article 18B, Paragraph (1), of the 1945 Constitution reads, “The State shall recognize and respect entities of regional administration that possess a specificity or a distinctiveness that are to be regulated by law”. Previously, the governance of special region was also regulated in the first version of the 1945 Constitution that was stipulated on August 18, 1945. In addition, it is contained in other constitutions that were formerly effective in Indonesia: the 1949 Constitution of the Republic of the United States of Indonesia, and the 1950 UUDS. The clearest arrangements regarding the status of special region were covered by the 1950 UUDS, whereas the 1945 and the 1949 Constitutions do not provide detailed description of special regional government units. This triggers some fundamental questions related to the substance of special region. This study reveals several facts related to the existence and administration of government in special regions. Among other things, the current arrangement does not open up the possibility of forming new special regions and the administration of special region only exists at the provincial level.Substansi Daerah Istimewa Menurut Undang-Undang Dasar Negara Republik Indonesia 1945 AbstrakNegara Republik Indonesia, berdasarkan Undang-Undang Dasar 1945, Amandemen ke-2, mengakui eksistensi Pemerintahan Daerah yang bersifat Istimewa. Pasal 18B, Ayat (1), UUD 1945 berbunyi, “Negara mengakui dan menghormati satuan-satuan pemerintahan daerah yang bersifat khusus atau bersifat istimewa yang diatur dengan Undang-undang”. Sebelumnya, pemerintahan daerah yang bersifat istimewa juga pernah diatur dalam UUD 1945 versi pertama yang ditetapkan 18 Agustus 1945, Konstitusi RIS 1949, dan UUDS 1950. Pengaturan yang jelas mengenai status daerah istimewa tertuang dalam UUDS 1950, sedangkan UUD 1945 dan Konstitusi RIS 1949 tidak memberikan penjelasan rinci mengenai satuan pemerintahan daerah yang bersifat istimewa. Hal tersebut memicu beberapa pertanyaan mendasar terkait makna daerah istimewa. Kajian ini menemukan beberapa fakta terkait eksistensi dan penyelenggaraan pemerintahan di daerah-daerah istimewa. Di antaranya, pengaturan yang ada saat ini tidak membuka kemungkinan pembentukan daerah-daerah istimewa yang baru dan pemerintahan daerah istimewa hanya ada di tingkat provinsi saja.DOI: https://doi.org/10.22304/pjih.v6n2.a6